Membangun karakter anak sejak dini melalui program Tetirah Bimasakti - Masturah, Alifah Nabilah; Rokhmah, Sakinah Nur; Prabowo, Adhyatman; Fasikhah, Siti Suminarti; Wulandari, Nany; Hermawaty, Yuni; Gunawan, Dwiko Nur Gunawan; Widodo, Agus Sri (Universitas Muhammadiyah Malang, 2024)
Elementary school children have the potential to develop positively with the support of their social environment. The more positive experiences presented in a child's daily life, the more likely they are to grow into well-adjusted individuals. The aim of this research is to evaluate the effectiveness of the Program Tetirah Bimasakti in reducing challenging behaviors in elementary school children. This study utilized a quasi-experimental, one-group pretest-posttest design. Participants included six children enrolled in the Program Tetirah Bimasakti, selected through purposive sampling. The research instrument employed was the Indonesian version of the Strengths and Difficulties Questionnaire (SDQ) for children. Data analysis was conducted using the paired sample t-test. The results indicated a decrease in the participants' difficulty scores; however, there was no significant change in their prosocial scores. This suggests that while the Program Tetirah Bimasakti was effective in reducing difficult behaviors, it was insufficient for fostering prosocial behavior. Consequently, this study implies that relevant institutions should develop structured modules for activity programs that can be tailored to specific and targeted competencies.